Pengaruh Minat dan Motivasi Belajar Terhadap Prestasi Belajar Matematika - Heriyati Heriyati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
The purpose of this study is to. Knowing the influence of learning motivation and interest towards the achievement of Junior High School students learn math in Karawaci subdistrict of Tangerang. The sample used in the 63 students who get with a random sampling technique. The collection of data by questionnaire (question form) to gauge interest and motivation to learn, while learning math achievement is taken from the value of the UAS. Test results whose hypotheses, namely 1) find out the influence of the interest and motivation of learning together towards the achievement of Junior High School students learn math in Karawaci subdistrict of Tangerang. 2) know how the learning interest towards the achievement of Junior High School students learn math in Karawaci subdistrict of Tangerang. 3) know how the learning motivation toward achievement of Junior High School students learn math in Karawaci subdistrict of Tangerang.